How Mainstream Politicians Erode Norms - Vicente Valentim; Elias Dinas; Daniel Ziblatt (British Journal of Political Science, 2025)
How does anti-immigrant rhetoric by mainstream politicians affect norms of tolerance? How does this compare to similar statements made by radical-right politicians? Drawing on experimental evidence, we find that statements by mainstream politicians lead to more norm erosion than similar statements by radical-right politicians. Subsample analyses suggest that this is because statements by mainstream-right politicians erode norm perceptions of right-wing individuals, while those by radical-right politicians induce backlash among left-wing individuals, who hold closer to the norm in place. The latter effect (backlash by the left) disappears when similar statements are made by mainstream right politicians. We argue that this difference occurs because mainstream politicians represent the views of a larger part of the population or have a higher status. Our results highlight the pivotal role of mainstream politicians in enforcing or eroding democratic norms, and that similar political statements can have different effects depending on their sender.
Keywords: 300; social norms; xenophobia; mainstream parties; accommodation; Germany